Effects of Platinum and Palladium Metals on Ni/\(Mg_1-xCe_x\) \(^4\)\(^+\)O Catalysts in the \(CO_2\) Reforming of Methane - Al-Doghachi, Faris A. J.; Jassim, Ali F. A.; Taufiq-Yap, Yun Hin (Challenges and Advances in Chemical Science Vol. 7, 2021)
Catalysts Ni/Mg1-xCex4+O and Ni,Pd,Pt/Mg1-xCex4+O were developed using the co-precipitation–impregnation methods. Catalyst characterization took place using XRD, H2-TPR, XRF, XPS, Brunauer–Emmett–Teller (BET), TGA, TEM, and FE-SEM. Testing the catalysts for the dry reforming of CH4 took place at temperatures of 700–900°C. Findings from this study revealed a higher CH4 and CO2 conversion using the tri-metallic Ni,Pd,Pt/Mg1-xCex4+O catalyst in comparison with Ni monometallic systems in the whole temperature ranges. The catalyst Ni,Pd,Pt/Mg0.85Ce4+0.15O also reported an elevated activity level (CH4; 78%, and CO2; 90%) and outstanding stability. Carbon deposition on spent catalysts was analyzed using TEM and Temperature programmed oxidation-mass spectroscopy (TPO-MS) following 200 h under an oxygen stream. The TEM and TPO-MS analysis results indicated a better anti-coking activity of the reduced catalyst along with a minimal concentration of platinum and palladium metals. The objective of this work is to examine the role of the Pt and Pd metals on the catalysts, as well as evaluating the stability of the catalysts and investigate the effects of reactant feed ratio, the catalysts concentration, the prepared catalysts conversion temperature, the efficacy of the catalysts in DRM process, and to inspect the enhancement of methane conversion through passing oxygen gas stream across the reaction.